Association study between matrix metalloproteinase‐3 gene (MMP3) polymorphisms and ankylosing spondylitis susceptibility. Issue 7 (23rd May 2019) - Zhu, Yong; Li, Shunan; Huang, Zhi; Xing, Wenhua; Li, Feng; Da, Yifeng; Xue, Jianmin; Li, Manglai; Sun, Ke; Jia, Haiyu; Yang, Xuejun
Abstract: Background: Ankylosing spondylitis (AS) is the second most common cause of inflammatory arthritis worldwide affecting the axial skeleton. Single nucleotide polymorphisms (SNPs) of matrix metalloproteinase‐3 (MMP3) in the development of AS has few been investigated in Chinese population. Methods: A total of 362 patients with AS and 362 healthy controls were enrolled in the study. Five SNPs in MMP3 genotypes were identified by Agena MassARRAY. Chi‐squared tests and genetic model were used to evaluate associations. Results: rs522616 had a significant risk of AS development compared to those with the TT genotype ( p  = 0.008). By multiple logistic regression models analysis, in codominant model, rs522616 CT genotypes also had a 1.44‐fold risk (95% CI = 1.06–1.96, p  = 0.008) for AS development compared to those with TT genotypes. In recessive model, the CC genotypes was a significantly reduced AS risk for individuals with TT/CT genotype (OR = 0.64; 95% CI = 0.41–0.99, p  = 0.040). Conclusion: The present study suggests that MMP3 rs522616 polymorphism is associated with AS susceptibility and MMP3 might be a potential diagnostic biomarker for AS. Further independent studies with larger cohorts are warranted to validate our findings in different populations. Abstract : The present study suggests that MMP3 rs522616 polymorphism is associated with AS susceptibility and MMP3 might be a potential diagnostic biomarker for AS. The polymorphisms identified in this study might be useful for predicting the susceptibility to the disease